Penyaring Air Keran untuk Pemenuhan Air Bersih di Desa Talangsuko, Kecamatan Turen, Kabupaten Malang - Layta Dinira; Mulyasuryani, Ani; Rumhayati, Barlah; Sabarudin, Akhmad (Rengganis Jurnal Pengabdian Masyarakat, 2025)
Desa Talangsuko, Kecamatan Turen, Kabupaten Malang is classified as an area with moderate risk of perilaku hidup bersih dan sehat (PHBS), indicating that PHBS management is not yet optimal. This community service aimed to improve household water management in Desa Talangsuko by implementing filtration and adsorption technology through tap water filters. The activities included water sampling, tap water filter design, education on clean water through counseling and hands-on demonstrations, and installation of tap water filters. The results showed an improvement in household water quality after the use of the tap water filters, as indicated by the reduction of chemical contaminants such as fluoride, nitrate, and water hardness. The counseling and hands-on demonstrations increased community awareness about clean water and the importance of regularly replacing water filter materials. These results suggest that this program demonstrated a positive impact on household water management in Desa Talangsuko.